VARIABEL YANG MEMPENGARUHI PEMILIHAN SALURAN DISTRIBUSI SALAK KRESIKAN KECAMATAN GONDANGWETAN KABUPATEN PASURUAN - Eri Yusnita Arvianti; Said Masduki (BUANA SAINS, 2008)
The aims of this research were to describe the market balancing variable influence, goods balancing, producer balancing, and distributor balancing toward the distributor channel choosing for zalacca in Pasuruan. Respondents were taken from the population using random simple sampling technique toward the zalacca farmer. The results showed that market balancing variable, goods balancing, producer balancing, and distributor balancing simultaneously influenced decision of distribution channel choosing of zalacca by farmers at the study area. The distributor balancing variable was the dominant factors influencing the decision of distribution channel choosing